On primary hyperideals of ternary hypersemiring - Nita Tamang; Manasi Mandal; Sampad Das (Journal of Hyperstructures, 2021)
In this article, we introduce the notions of radical of hyperideals and primary hyperideals of a ternary hypersemiring.We obtain some important properties of radical of hyperideals and primary hyperideals on a particular class of hyperideals, called Cternary hyperideals in ternary hypersemirings. We also generalize the concept of prime and primary avoidance theorem in ternary hypersemirings for C-ternary hyperideals.